Haematuria on the Spanish Registry of Glomerulonephritis - Yuste, Claudia (Sci Rep, 2016)
Recent studies suggest a pathogenic role for glomerular haematuria among renal function. However, there is no data on the prevalence of haematuria from a large renal biopsy registry. We analysed the prevalence of gross (GH) and microscopic (mH) haematuria in 19,895 patients that underwent native renal biopsies from the Spanish Registry of Glomerulonephritis. Haematuria’s overall incidence was 63% (GH 8.6% and mH 55.1%), being more frequent in males (64.7% vs. 62.4%). GH was more prevalent in patients <18 years (21.3% vs. 7.7%). The commonest clinical presentation associated with GH was acute kidney injury (31.5%) and IgA Nephropathy (IgAN) (33.6%) was the most frequent histological finding. GH patients showed a significantly (p < 0.05) lower eGFR and proteinuria levels as compared with patients with mH and without haematuria. Moreover, mH was more prevalent in adults (56.3%). Nephrotic syndrome was the commonest clinical presentation in mH patients (32.2%) and IgAN (18.5%) the most frequent histological finding. In conclusion, haematuria, is a frequent urinalysis finding in patients underwent native renal biopsy. The most frequent histological finding in both GH and mH is IgAN. Whereas, GH is more frequent in young males with acute kidney injury, mH is commoner among adults with nephrotic syndrome.